PENGENALAN DAN PENERAPAN DASAR ADOBE PREMIERE BAGI SISWA SMK ISLAM GARDEN SCHOOL SEBAGAI UPAYA PENGUATAN SOFT SKILL DI ERA DIGITAL - Afcharina Diniyil Muhlisin; Zaehol Fatah (CV. Denasya Smart Publisher, 2025)
This study aims to describe the process of basic video editing training using Adobe Premiere as a medium to strengthen the non-technical skills (soft skills) of vocational high school (SMK) students. The research method used is descriptive qualitative, conducted through a two-day seminar and hands-on practice. The training materials included an introduction to the Adobe Premiere interface, basic video editing tools, and skill implementation through group projects. The results showed improvement not only in students’ technical abilities in video editing but also in the development of soft skills such as teamwork, time management, visual communication, and creativity. Students responded positively, and teachers considered the training effective for integrating technology, creative expression, and project-based learning. Overall, the training not only introduced Adobe Premiere as a technical tool but also served as a platform for strengthening soft skills that are relevant to the demands of the digital-era workforce.